2021
DOI: 10.1037/abn0000621
|View full text |Cite
|
Sign up to set email alerts
|

Face perception predicts affective theory of mind in autism spectrum disorder but not schizophrenia or typical development.

Abstract: Autism spectrum disorder (ASD) and schizophrenia spectrum disorder (SCZ) have overlapping symptomatology related to difficulties with social cognition. Yet, few studies have directly compared social cognition in ASD, SCZ, and typical development (TD). The current study examined individual differences in face recognition and its relation to affective theory of mind (ToM) in each diagnostic group. Adults with ASD (n = 31), SCZ (n = 43), and TD (n = 47) between the ages of 18 and 48 years-old with full scale IQ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
7
0
1
Order By: Relevance
“…Studies examining emotion recognition in children and adolescents with ASD, ADHD, or SCZ showed overall inconclusive results. Some studies showed that the recognition of basic emotions in those psychiatric disorders seems to be similar to that of neuro-typical controls [ASD: ( 22 26 ); ADHD: ( 27 , 28 ); SCZ: ( 29 31 )], while other have revealed recognition difficulties [ASD: ( 23 , 32 , 33 ); ADHD: ( 34 36 ); SCZ: ( 37 39 )]. The inconsistency of results can be attributed to various methodological aspects (e.g., complexity of the task, time pressure, different stimuli and dependent variables) as well as sample heterogeneity [ASD: ( 40 ); ADHD: ( 41 ); SCZ: ( 42 )].…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining emotion recognition in children and adolescents with ASD, ADHD, or SCZ showed overall inconclusive results. Some studies showed that the recognition of basic emotions in those psychiatric disorders seems to be similar to that of neuro-typical controls [ASD: ( 22 26 ); ADHD: ( 27 , 28 ); SCZ: ( 29 31 )], while other have revealed recognition difficulties [ASD: ( 23 , 32 , 33 ); ADHD: ( 34 36 ); SCZ: ( 37 39 )]. The inconsistency of results can be attributed to various methodological aspects (e.g., complexity of the task, time pressure, different stimuli and dependent variables) as well as sample heterogeneity [ASD: ( 40 ); ADHD: ( 41 ); SCZ: ( 42 )].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Altschuler et al ( 2021 ), 2 Booules-Katri et al ( 2019 ); 3 Couture et al ( 2010 ); 4 Kandalaft et al ( 2012 ); 5 Lugnegård et al ( 2013 ); 6 Pinkham et al ( 2020 ); 7 Boada et al ( 2020 ); 8 Veddum et al ( 2019 ); 9 Eack et al ( 2013 ); 10 Kuo et al ( 2019 ); 11 Nakata et al ( 2020 ); 12 Graux et al ( 2019 ); 13 Martinez et al ( 2017 ); 14 Dubreucq et al ( 2022 ); 15 Tobe et al ( 2016 ). …”
Section: Resultsunclassified
“…To diagnose SSD, 14 studies used SCID/SCID-II, 2 studies used DIGS, and 5 studies did not specify the diagnostic method. Only 4 studies conducted a sufficient differential diagnostic assessment of both their SSD and the ASD group (Altschuler et al, 2021 ; Boada et al, 2020 ; Martinez et al, 2017 ; Martinez et al, 2019 ). The remaining 17 studies (81%) used apparently solely an insufficient, specialized diagnostic method (AAA, ADOS, ADI, or DISCO) to diagnose ASD, meaning these 17 studies did not conduct a comprehensive differential diagnostic assessment of this group.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, there is a long-standing debate in the literature about how ToM should be defined and measured. Especially, there is criticism of the RMET, which is based on the ability to recognize complex emotional states rather than reason with affective mental states [ 66 ]. Second, our study only focused on affective and cognitive components of ToM, although an increasing amount of evidence suggests the multifaced nature of ToM [ 67 ].…”
Section: Discussionmentioning
confidence: 99%